Art and place-based education - Ásthildur Jónsdóttir (University of Aberdeen, School of Education, 2013)
Icelandic teachers face complex challenges with an increasing emphasis on sustainability being demanded by the curriculum. This new demand calls for more critical approaches as teachers meet diverse student needs. Place-based education can offer a way of responding to the challenges. Teachers need to construct learning experiences that equip students with knowledge, which enables them to develop values that lead to more sustainable lifestyles. This paper describes the nature and impact of different aspects of art in the context of place-based education. The purpose of this inquiry is to examine what artistic place-based education has to offer education for sustainability (ES). Ideas are discussed on how to create settings and design activities that give art students an incentive to achieve an understanding of sustainability. The terms quality of life and well-being are discussed in relation to the possibilities that art education provides for students to better understand their own space and place in time. Examples are taken from art in Iceland and elsewhere.